Hybrid Teacher Training in Arduino-based Science Education across Different Modalities - Lia Laela Sarah; Greg Shaw; Andi Suhandi; Ida Kaniawati; Mubiar Agustin (Science Education International)
In science education, educators frequently encounter the challenges of inadequate resources, equipment, and pedagogical strategies when planning and executing science projects in classrooms. To address this pervasive issue, forty-one science teachers participated in a training workshop to acquire expertise using Arduino microcontrollers and sensors as instrumental tools for scientific educational experiments. Of the participants, 18 engaged in face-to-face instruction, while others embraced online learning through synchronousplatforms, such as Zoom, and asynchronous media, such as Google Classroom. The training consisted of three sections, including science pedagogy and the Arduino context for each session. To evaluate the training results, science teacher participants had to complete the assignment in the pedagogical context and the Arduino science project. Our findings illuminate a disparity in completion rates between online and face-to-face modes of instruction, with 41% of teachers succeeding in the former and a notably higher 79% in the onlineform. This study underscores the nuanced challenges encountered when incorporating teaching tools into science education activities, irrespective of the instructional mode. The challenges that participants faced included effective translation of wiring diagrams to physical circuits, resolution of coding errors, mitigation of connectivity issues between the Arduino equipment and computers, and challenges in structuring instructional steps that are essential for the successful implementation of Arduino-based science teaching. Nevertheless,85% of educators expressed a shared perspective on the viability of Arduino tools as instruments for enriching the landscape of science education.